2007
DOI: 10.1128/iai.01737-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Prepore Large-Complex Stage in the Mechanism of Action of Clostridium perfringens Enterotoxin

Abstract: Clostridium perfringens enterotoxin (CPE) is the etiological agent of the third most common food-borne illness in the United States. The enteropathogenic effects of CPE result from formation of large CPEcontaining complexes in eukaryotic cell membranes. Formation of these ϳ155-and ϳ200-kDa complexes coincides with plasma membrane permeability changes in eukaryotic cells, causing a Ca 2؉ influx that drives cell death pathways. CPE contains a stretch of amino acids (residues 81 to 106) that alternates markedly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 40 publications
4
102
0
Order By: Relevance
“…[15][16][17] The targeted action of CPE is mediated by binding to a subset of claudins, mainly to claudin-3 and -4, which are frequently overexpressed in epithelial tumors. 22,24,25 This binding leads to disintegration of plasma membrane in association with rapid cytolysis of treated cells. 34 Several in vitro and in vivo studies demonstrated the antitumoral activity of recombinant CPE, limited by the need for frequent, repeated CPE application to achieve antitumoral effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] The targeted action of CPE is mediated by binding to a subset of claudins, mainly to claudin-3 and -4, which are frequently overexpressed in epithelial tumors. 22,24,25 This binding leads to disintegration of plasma membrane in association with rapid cytolysis of treated cells. 34 Several in vitro and in vivo studies demonstrated the antitumoral activity of recombinant CPE, limited by the need for frequent, repeated CPE application to achieve antitumoral effects.…”
Section: Discussionmentioning
confidence: 99%
“…These insert into the plasma membrane, leading to the loss of osmotic equilibrium and cell death. [20][21][22] CPE binds to a subset of the claudin family of tight junction proteins, such as claudin-3 and -4, initially defined as CPE receptors. 23 The C-terminus of CPE permits this binding, whereas the N-terminus of CPE is rather associated with cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that fact that the C-Cpe peptide no longer contains direct cytotoxic activity, a recent report showed that a similar size truncated version of Cpe still retained the ability to form membrane "prepore complexes," suggesting that this peptide retained the ability to form structures distinct from its ability to simply bind the second extracellular domain of Cldn-4 (18,19). Some studies also showed binding by the smaller Cpe30 peptide, but our present studies show that Cpe peptides as small as Cpe17 also can bind with high affinity, and even shorter versions, such as a mutated version (MT2) only 12 amino acids long could still bind with high affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those structural analyses, coupled with mutagenesis studies (56)(57)(58)(59)(60)(61), indicated that CPE contains a C-terminal domain that binds to claudin receptors on host cells and an N-terminal domain, consisting of two halves, that is critical for pore formation by mediating oligomerization and membrane insertion.…”
Section: Toxins That Can Be Either Chromosomally or Plasmid Encodedmentioning
confidence: 99%
“…At 37°C, CPE in a small complex rapidly oligomerizes on the membrane surface to form a large (ϳ450-kDa) prepore complex named CPE hexamer 1 (CH-1) (59,66,74). In addition to six copies of the toxin, CH-1 contains both receptor and nonreceptor claudins (the presence of nonreceptor claudins in CH-1 likely reflects a propensity for claudin-claudin interactions) (66).…”
Section: Toxins That Can Be Either Chromosomally or Plasmid Encodedmentioning
confidence: 99%